MFG-E8 Maintains Cellular Homeostasis by Suppressing Endoplasmic Reticulum Stress in Pancreatic Exocrine Acinar Cells - Ren, Yifan; Liu, Wuming; Zhang, Jia; Bi, Jianbin; Fan, Meng; Lv, Yi; Wu, Zheng; Zhang, Yuanyuan; Wu, Rongqian (Frontiers in Cell and Developmental Biology, 2022)
Excessive endoplasmic reticulum (ER) stress contributes significantly to the pathogenesis of exocrine acinar damage in acute pancreatitis. Our previous study found that milk fat globule EGF factor 8 (MFG-E8), a lipophilic glycoprotein, alleviates acinar cell damage during AP via binding to αvβ3/5 integrins. Ligand-dependent integrin-FAK activation of STAT3 was reported to be of great importance for maintaining cellular homeostasis. However, MFG-E8’s role in ER stress in pancreatic exocrine acinar cells has not been evaluated. To study this, thapsigargin, brefeldin A, tunicamycin and cerulein+LPS were used to induce ER stress in rat pancreatic acinar cells in vitro. L-arginine- and cerulein+LPS-induced acute pancreatitis in mice were used to study ER stress in vivo. The results showed that MFG-E8 dose-dependently inhibited ER stress under both in vitro and in vivo conditions. MFG-E8 knockout mice suffered more severe ER stress and greater inflammatory response after L-arginine administration. Mechanistically, MFG-E8 increased phosphorylation of FAK and STAT3 in cerulein+LPS-treated pancreatic acinar cells. The presence of specific inhibitors of αvβ3/5 integrin, FAK or STAT3 abolished MFG-E8’s effect on cerulein+LPS-induced ER stress in pancreatic acinar cells. In conclusion, MFG-E8 maintains cellular homeostasis by alleviating ER stress in pancreatic exocrine acinar cells.